Reducing energy demand by the combined application of advanced control strategies in a full scale WWTP - G. Bertanza; P. Baroni; S. Garzetti; F. Martinelli (Water Science and Technology, 2021)
Two advanced control strategies were applied in the secondary and tertiary stages, respectively, of a full scale wastewater treatment plant (WWTP). This has a nominal capacity of 330,000 population equivalent (PE), a complex configuration (having been upgraded several times through the years), and it faces significant seasonal load fluctuations (being located in a touristic area, in Northern Italy). The lifting station of the tertiary treatments (devoted to phosphorus precipitation and UV disinfection) was optimized by adjusting the pumped flowrate, depending on influent phosphorus concentration. A preliminary simulation showed that a 15% reduction of pumping energy could be achieved. This result was confirmed by field measurements. Moreover, a fuzzy control system was designed and applied to one of the six parallel nitrification reactors, yielding a reduction of more than 25% of the power requirement for aeration. Overall, the combined application of the two controllers led to a 7% reduction of the total energy consumption of the plant. This result is particularly promising given that the fuzzy controller was applied only to one of six biological reactors. HIGHLIGHTS Smart control strategies are required for WWTPs: fuzzy logic was adopted for aeration.; Full scale demonstrations of control strategies are rarely described in the literature.; A significant energy demand reduction has been achieved in a real scale WWTP.; The potential of plant-wide application of combined control strategies has been demonstrated.; The designed controllers are highly adaptable, favouring applicability in other plants.;